Qualitative evaluation of a guideline supporting shared decision making for extreme preterm birth. (18th March 2020) - Moore, Gregory; Reszel, Jessica; Daboval, Thierry; Lemyre, Brigitte; Barker, Conor; Dunn, Sandra
Abstract: Background and objectives: The decision to attempt resuscitation or provide palliative care at birth for extremely preterm infants between 22 and 25 weeks remains complex. The purpose of this study was to identify facilitators and barriers to implementation of a clinical practice guideline developed to support shared decision-making for these cases. Methods: A purposeful sample of healthcare providers, involved in the care of one of five cases of anticipated extremely preterm birth, was recruited for interviews. Participants shared their views on the guideline content, implementation process, and facilitators and barriers encountered. Interviews were audio-recorded and transcribed verbatim. Qualitative content analysis was used to code, categorize, and thematically describe the data. The Knowledge-Attitudes-Behaviours framework was used to organize the findings. Results: Twenty-five key informants (16 physicians, nine nurses) were interviewed. Participants described varying levels of knowledge of the guideline. Facilitators to implementation included: (1) an awareness of, familiarity with and belief in the content; (2) hard copy and electronic guideline accessibility; and, (3) institutional expertise to provide necessary care. Barriers included: (1) minimal awareness or familiarity with the content; (2) lack of agreement with the recommendations; (3) inadequate evidence and applicability to support changes in practice; and, (4) lack of resources to care for the most immature infants. Conclusions: Identified facilitators and barriers will inform the development of tailored strategies for improved local and future broader implementation. Other institutions can use the results to facilitate implementation of their guidelines on this ethically charged area.